The Resilience of Sharia and Conventional Banks in Indonesia during the Covid-19 Pandemic Crisis - Nur Hidayah; Ainun Zamilah; Sofyan Rizal; Jaharuddin Jaharuddin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. This study aims to analyze the effect of COVID-19 on banking resilience in Indonesia and to investigate whether there are differences in the effect of COVID-19 on Islamic and conventional banks. Using panel regression with robust standard error on 38 conventional banks and sharia banks going public in Indonesia, covering the period before the COVID-19 pandemic (Q3 2018-Q4 2019) and during the COVID-19 pandemic (Q1 2020 – Q2 2021), it shows that the existence of the covid-19 crisis has a significant effect on all bank financial performance indicators, but not significant on all bank risk indicators. Using the independent t-Test test with the assumption of unequal variance and Welch correction, this study conducts a comparative test based on six panels of criteria and found that Islamic banks are more resilient than conventional banks.Keywords: Resilience, Bank Financial Performance, Bank Risk, Covid-19 Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh COVID-19 terhadap resiliensi perbankan di Indonesia dan menginvestigasi apakah terdapat perbedaan pengaruh COVID-19 terhadap resiliensi bank syariah dan konvensional. Menggunakan regresi panel dengan Robust standard error pada 38 bank konvensional dan bank syariah yang sudah ‘go public’ di Indonesia, meliputi periode sebelum pandemi COVID-19 (Q3 2018-Q4 2019) dan selama pandemi COVID-19 ( Q1 2020 – Q2 2021), studi ini menunjukkan bahwa keberadaan krisis covid-19 berpengaruh signifikan terhadap semua indikator kinerja keuangan bank, dan tidak signifikan terhadap semua indikator risiko bank. Dengan menggunakan uji Independent t-Test dengan asumsi unequal variance dan Welch correction, penelitian ini melakukan uji komparatif berdasarkan enam panel kriteria dan diperoleh kesimpulan bahwa bank syariah lebih tangguh dibandingkan bank konvensional.Kata kunci: Ketahanan, Kinerja Bank, Risiko Bank, Covid-19